2016
DOI: 10.1007/s00775-016-1414-3
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ferryl-mediated hydroxylation: 40 years of the rebound mechanism and C–H activation

Abstract: Since our initial report in 1976, the oxygen rebound mechanism has become the consensus mechanistic feature for an expanding variety of enzymatic C–H functionalization reactions and small molecule biomimetic catalysts. For both the biotransformations and models, an initial hydrogen atom abstraction from the substrate (R–H) by high-valent iron-oxo species (Fen=O) generates a substrate radical and a reduced iron hydroxide, [Fen−1–OH ·R]. This caged radical pair then evolves on a complicated energy landscape thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
249
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(265 citation statements)
references
References 225 publications
3
249
0
Order By: Relevance
“…In this context, it must be emphasized that our microsome and hepatocyte incubations, which certainly hydroxylate CDZ173 based on cytochrome P450, non‐heme diiron hydroxylases and α ‐keto‐glutarate dependent non‐heme iron hydroxylases following an oxygen rebound mechanism are incompatible with the mechanism proposed for a Crabtree ‐type catalyst. If α ‐keto‐glutarate dependent non‐heme iron halogenases following a non‐oxygen rebound mechanism are present in our assays is not addressed.…”
Section: Summary Conclusion and Outlook For 3h‐labelling Strategiesmentioning
confidence: 99%
“…In this context, it must be emphasized that our microsome and hepatocyte incubations, which certainly hydroxylate CDZ173 based on cytochrome P450, non‐heme diiron hydroxylases and α ‐keto‐glutarate dependent non‐heme iron hydroxylases following an oxygen rebound mechanism are incompatible with the mechanism proposed for a Crabtree ‐type catalyst. If α ‐keto‐glutarate dependent non‐heme iron halogenases following a non‐oxygen rebound mechanism are present in our assays is not addressed.…”
Section: Summary Conclusion and Outlook For 3h‐labelling Strategiesmentioning
confidence: 99%
“…We initiated our studies by analyzing two reactions from the field of bioinorganic chemistry [14] where C(sp 3 )ÀHb ond oxidation occurs either via cPCET,f ollowing the above definition, or aH AT mechanism. Fort he cPCET case,w e selected the well-studied reaction of lipoxygenase, [15] an Fe III À OH active site which breaks one of the C(sp 3 ) À Hb onds of arachidonic acid, and for HATw es elected the C(sp 3 ) À H oxidation event from the oxoiron(IV) intermediate in taurine dioxygenase (TauD-J), [16] which oxidizes aC(sp 3 )ÀHbond of taurine.S tructural depictions for the active sites and transition states for CÀHb ond activation are shown in Figure 1.…”
mentioning
confidence: 99%
“…Reactions with substrates 2, 3,a nd 9 demonstrate that the electronic properties of the OxyC reaction are finely tuned. [21][22][23] Cpd Im ay oxidize Hpg3 to yield compound II (cpd II) and the phenolic radical (12), which has significant spin density at the ortho position. [21][22][23] Cpd Im ay oxidize Hpg3 to yield compound II (cpd II) and the phenolic radical (12), which has significant spin density at the ortho position.…”
mentioning
confidence: 99%
“…To guide future studies,wepropose the working model shown in Figure 3f,i nw hich reaction of the resting state of the enzyme (10)w ith O 2 and substrate gives rise to compound I (cpd I, 11), as is typical for P450 enzymes. [21][22][23] Cpd Im ay oxidize Hpg3 to yield compound II (cpd II) and the phenolic radical (12), which has significant spin density at the ortho position. Addition into the aromatic system of Dpg delivers the stabilized intermediate 13,which, based on first principles, is more stable than an intermediate that would result from addition of aDpg radical to Hpg.…”
mentioning
confidence: 99%